Exploring the link between serum uric acid and endometriosis: a cross-sectional analysis utilizing NHANES data from 1999-2006 - Chen, Haiwei; Chen, Yuling; Chen, Xiaotong; Tang, Lixin; Liu, Jiaqi; Shi, Wen-Jing; Ou, Yu-Hua (Frontiers in Endocrinology, 2025)
BackgroundSubstantial impacts on the female reproductive system have been definitively linked to heightened levels of serum uric acid. However, evidence directly linking increased serum uric acid levels to endometriosis in women remains sparse, and the precise characteristics of this influence are still not fully understood.ObjectiveTo explore the exact relationship between serum uric acid and endometriosis.Study designReferencing the data accumulated from the National Health and Nutrition Examination Survey (NHANES), this study covers the period from 1999 to 2006, conducted an analysis of 5,162 female participants aged 20 to 54 years (representing a sample size of approximately 66,927,890 women). The study adopted a cross-sectional methodology to delve into the tie between serum uric acid and the prevalence of endometriosis. Utilizing rigorous methodologies, including weighted multivariable logistic regression models, subgroup analyses, and statistical methodologies for smooth curve fitting.ResultsA positive association was found between continuous serum uric acid and the risk of endometriosis (OR = 1.25, 95% CI [1.09, 1.44], P = 0.003). At the same time, women in the highest quartile had a 133% higher risk of endometriosis compared with women with the lowest quartile of uric acid (OR=2.33,95%CI [1.28, 4.23], P=0.009). At the same time, smooth curve fitting also found a linear positive correlation between serum uric acid and endometriosis. There was no heterogeneity in subgroup analysis.ConclusionThe study indicates a strong link between increased serum uric acid levels and the appearance of endometriosis in women. Specifically, women with elevated uric acid levels face a higher likelihood of developing endometriosis.